Top Scholar - Lifetime, by ScholarGPS - Demetriou, Demetris (My University, 2026)
Top Scholar - Lifetime: Your strong publication record, the impact of your work, and the notable quality of your scholarly contributions have placed you in the top 0.5% of all scholars worldwide according to the most recent 2024 ScholarGPS rankings. #217 Decision support system This year's rankings are based on the ScholarGPS database of over 30 million Scholar Profiles and 120,000 Institutional Profiles.
Keywords: Worlds Top Scientists